Potential use of essential oils in cosmetic and dermatological hair products: A review - Abelan, Ursulandréa Sanches [UNESP]; de Oliveira, Andressa Costa; Cacoci, Érica Savassa Pinto; Martins, Tércio Elyan Azevedo; Giacon, Virginia Mansanares; Velasco, Maria Valéria Robles; Lima, Cibele Rosana Ribeiro de Castro (Wiley, 2022)
Background: Essential oils have great interest among the increasing demand for herbal cosmetics in the market. They are natural sources of biologically active ingredients due to the wide application of such compounds as well as their particular chemical composition. Several researches have evaluated the effectiveness of these bioactive ingredients for use in cosmeceuticals, mainly in both hair scalp and shaft hair damage repair. Thus, the amounts and their associations define the properties of these compositions with interest for hair cosmetic use, such as antioxidant, inflammatory, and antimicrobial activities. Because they are complex compounds, their actions on the skin, hair scalp, and shaft are not yet fully understood. Aims: The purpose of this review is to highlight the relevant researches and findings on essential oils in hair care. Methods: In order to achieve this objective, the present work comprises an updated bibliographic review related to essential oils used in hair care. Results: It was possible to observe that cosmeceuticals containing essential oils applied to the scalp are preferable for topical activity. Also, it was noticed that there are few reports regarding their use in hair shaft. However, it was found that some oils are used to intensify the brightness and fix the hair color. Conclusions: This work demonstrated that the use of essential oils in both cosmetic products (industrial application) and those associated with oils carriers (as individual protocols) may lead to satisfactory results in the treatment of some scalp dysfunctions.
Keywords: cosmeceutical; essential oil; hair; hair care